Damaged building after the 1906 earthquake. - Unknown:::Creator::::::::::::
Photograph shows damaged buildings after the 1906 earthquake along with pedestrians walking by and one individual on a bicycle. A carriage with the sign "Pacific Transfer and Storage Co." is parked alongside a damaged building.